Assembling social innovations in emergent professional communities. The case of learning region policies in Germany. Issue 3 (3rd March 2020) - Füg, Franz; Ibert, Oliver
ABSTRACT: In this paper, we use the notion social innovation to shed light on the complex interrelations between the emergence and consolidation of new policy approaches and their geographical mobility. Empirically, the paper deals with learning region policies in Germany, which epitomize a shift of the main approach from 'catching up' to 'reflexive experimentation' during the 1980s/1990s in Germany. We highlight the nature of social innovations in spatial planning as complex assemblages of material, organizational and conceptual elements. These elements are not necessarily new themselves. Rather, the novelty lies in the unprecedented ways, in which these elements are re-combined. From an innovation perspective, the unfolding of the learning region policy model co-evolves with the growth and proliferation of a related professional community of practice. Longitudinal data covering the whole innovation process is analysed in combination with case study material from two recent instantiations of the respective policies: the REGIONALE 2016 Westmünsterland and the 'Competition Impulse Regions' in Saxony.